Synthesis, electrochemistry and in situ Spectroelectrochemistry of soluble lead phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The synthesis, characterization and voltammetric and spectroelectrochemical properties of newly synthesized lead phthalocyanines bearing tetra-(1,1-(dicarbopenthoxy)-2-(4-biphenyl)-ethyl), tetra-(1,1-(dicarbpenthoxy)-2-(1-naphthyl)-ethyl and tetra-((1,1,2-(tricarbopentoxyethyl)) substituents have been presented in this work for the first time. The characterization of the complexes was made by elemental analysis, H-1 NMR, FT-IR, UV-vis and Maldi-TOF The solution redox properties and spectroelectrochemical investigation of the complexes are studied using various electrochemical techniques in DCM oil a platinum electrode. Cyclic voltammetry and differential pulse voltammetry studies show that the complexes give three one-electron ligand-based reductions and two one-electron oxidation couples having diffusion-control led mass transfer character. Assignments of the redox couples were confirmed by spectroelectrochemical measurements. Spectroelectrochemical studies reveal that all complexes are demetallized during the spectroelectrochemical measurement under the applied potentials at the first reduction and oxidation potentials of the complexes. Different ring substituents of the complexes affect the easy demetallization processes of the complexes. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; lead; cyclic voltammetry; spectroelectrochemistry; demetallization; THIN-FILMS; DEMETALATION; SPECTRA; COBALT; COPPER; GAS